Who gains more from networking? A comparative study of Polish exporting and non-exporting SMEs - Lidia Danik; Dominika Mirońska (International Journal of Management and Economics, 2022)
Paper's objectives: The paper aims to identify differences in the perceived benefits of cooperation in domestic and foreign networks achieved by Polish small and medium enterprise (SME) exporters and non-exporters. Methods applied: A quantitative study was conducted using computer-assisted telephone interviewing and computer-assisted web interviewing on 240 Polish exporting and non-exporting SMEs. The t-test and correlation analysis were used to investigate the phenomena under study. Findings: While exporting SMEs attach greater importance to networking with foreign partners than non-exporting ones, domestic partners are of equal importance for exporting and non-exporting firms. Exporting SMEs perceive local business partners to have more influence on their market success than foreign ones. Exporting SMEs benefit more from networking than non-exporting companies. Originality/value: The paper compares the importance of local and foreign network partners for the market success of exporting and non-exporting SMEs, contributing to both internationalization and entrepreneurial literature.
Keywords: M16; F23; 650; exporters; networking; Poland; SMEs